A PHENOMENOLOGICAL STUDY OF HOW WOMEN EXPERIENCE AND UNDERSTAND LUXURY IN SPORT SHOES AND THEIR PURCHASE INTENTION TOWARDS IT - LENANTA, BUNGA ANNISA (Jurnal Ilmiah Mahasiswa FEB, 2018)
The purposes of this research are to define the meaning of luxury sport shoes and to construct concept of women purchase intention towards luxury sport shoes. The background of this research is based on the phenomena found in the field of fitness lifestyle, where women show unique buying behavior of sport shoes, in which mostly preferably by men. This research done using phenomenological method through five steps of analysis: epoche, phenomenological reduction, imaginative variation, textural and structural description, and synthesis of meaning. Further, finding of the research also tied up with theories. Data collection method was done through in-depth interview and observation. The result revealed the meaning of luxury in sport shoes, which is because of its expensiveness that constructed by the price, exclusivity, brand, and appearance. It also found that women purchase intention towards luxury sport shoes are defined in three steps. First is the utilitarian intention with the most participants, second is the hedonic intention, and the third with the lowest number of participants is the conspicuous intention. In which drawn in triangle shape. Further findings also revealed that reference group has major influence to women purchase intention toward luxury sport shoes. Key  Words:  Phenomenology,  purchase  intention,  women,  luxury,  reference group